Penggunaan Salam Smart dalam Meningkatkan Kesehatan Mental dan Penerapan Protokol Kesehatan pada Kelompok Pengajian - Tri Rejeki Andayani; Budiyanti Wiboworini; Nanang Wiyono; Farida Hidayati (Badan Perencanaan Pembangunan Daerah (BAPPEDA) Kabupaten Pati, 2021)
ENGLISHThe covid-19 pandemic that has occurred for a long time brings changes in the entire order of human life, including religion. Religious and social activities, like